Biomechanical analysis of the spike motion for world-class male volleybal players - Quispe Marquez, W.; Masumura, M.; Ae, M.; Endo, T.; Yasuda, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The front spike is the most frequently used technique to obtain a point in volleyball, but there is little specific information on the spike motion for elite players during games. That warrants understanding of the mechanism of this motion and an evidencebased coaching. The purpose of this study was to analyze and compare the spike motions of world-class male volleyball players who participated in the Men`s World Championship 2006.